People construct simplified mental representations to plan - Ho, Mark K.; Abel, David; Correa, Carlos G.; Littman, Michael L.; Cohen, Jonathan D.; Griffiths, Thomas L. (Nature (London), 2022)
One of the most striking features of human cognition is the ability to plan. Two aspects of human planning stand out—its efficiency and flexibility. Efficiency is especially impressive because plans must often be made in complex environments, and yet people successfully plan solutions to many everyday problems despite having limited cognitive resources 1 – 3 . Standard accounts in psychology, economics and artificial intelligence have suggested that human planning succeeds because people have a complete representation of a task and then use heuristics to plan future actions in that representation 4 – 11 . However, this approach generally assumes that task representations are fixed. Here we propose that task representations can be controlled and that such control provides opportunities to quickly simplify problems and more easily reason about them. We propose a computational account of this simplification process and, in a series of preregistered behavioural experiments, show that it is subject to online cognitive control 12 – 14 and that people optimally balance the complexity of a task representation and its utility for planning and acting. These results demonstrate how strategically perceiving and conceiving problems facilitates the effective use of limited cognitive resources. Strategically perceiving and conceiving problems facilitates the effective use of limited cognitive resources.